1985
DOI: 10.1104/pp.79.4.996
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Adjustment by Intact Isolated Chloroplasts in Response to Osmotic Stress and Its Effect on Photosynthesis and Chloroplast Volume

Abstract: Spinach leaf chloroplasts isolated in isotonic media (330 millimolar sorbitol, -1.0 megapascals osmotic potential) had optimum rates of photosynthesis when assayed at -1.0 megapascals. When chloroplasts were isolated in hypertonic media (720 millimolar sorbitol, -2.0 megapascals osmotic potential) the optimum osmotic potential for photosynthesis was shifted to -1.8 megapascals and the chloroplasts had higher rates of COrdependent O2 evolution than chloroplasts isolated in 330 millimolar sorbitol when both were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 16 publications
3
23
0
Order By: Relevance
“…Recently, a correlation between protoplast volume and photosynthetic capacity has been demonstrated in intact leaves of growth chamber-grown wheat (21). The existence of an apparent optimum protoplast volume for maximal photosynthetic activity in coffee is in agreement with results from in vitro studies cited above (7,20). The optimal relative symplast volume for maximum A in coffee was approximately 0.94, above which A declined by about 40% at maximum symplast volume attained at midday under field conditions (Fig.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Recently, a correlation between protoplast volume and photosynthetic capacity has been demonstrated in intact leaves of growth chamber-grown wheat (21). The existence of an apparent optimum protoplast volume for maximal photosynthetic activity in coffee is in agreement with results from in vitro studies cited above (7,20). The optimal relative symplast volume for maximum A in coffee was approximately 0.94, above which A declined by about 40% at maximum symplast volume attained at midday under field conditions (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Previous in vitro studies carried out with isolated chloroplasts (2,20) and leaf slices (7) have led others to conclude that inhibition of photosynthesis in water-stressed plants may be largely attributable to reduced chloroplast volume. It has also been suggested that drought-induced alterations in the protoplast, and therefore chloroplast volume-IL relationship may serve to maintain photosynthetic activity during drought (23).…”
Section: Discussionmentioning
confidence: 99%
“…Some considerations are summarized below. First, measurement of the ion content for dark-adapted chloroplasts indicated K + being the major monovalent cation (160-200 mM), which could be replaced by Na + (40-70 mM), and Cl À as the major anion (100 mM) [35]. In the same report, the major fraction of these ions was found in the stroma since only 10%, 5-10% and 10-20% of the above concentrations of K + , Na + and Cl À were found inside the thylakoid lumen.…”
Section: Could Aquaporins Be Beneficial For Thylakoid Membranes?mentioning
confidence: 99%
“…The same is presumably true of C S across organelle membranes, where metabolism and transport activities in both the organelle and the cytoplasm can produce substantial differences in solute content. Organelles have been shown to change shape and volume in response to alterations in environmental osmolarity and during metabolic activity (Robinson, 1985;Gupta and Berkowitz, 1987;McCain, 1995;Boustany et al, 2002;Finan et al, 2009), suggesting that they can undergo osmoregulation from within the cell cytoplasm. However, the molecular details of organellar osmoregulation and how it might be integrated into the larger Figure 6.…”
Section: Discussionmentioning
confidence: 99%